UNUSUAL CATCHES OF THl FLYINGFISH, EAREXOCOETliS BRACHYPTERVS BRACHYPTERVS (RICHARDSON) IN INSHORE WATERS AT MADRAS - Rao, K Satyanarayana; Basheerudheen, S (Indian Journal of Fisheries, 2011)
Unusually large catches of the flyingfish Parexocoetus brachyplerus brachypterus (Richardson) caught in the inshore waters of Madras coast between February and April, 1969 are repotted. The morphological features, size-composition, sex-ratio, stages of maturity and food of the flyingfish have been studied. The probable factors responsible for the sudden appearance of the flyingfish in large numbers in the inshore waters have been discussed.